American sniper : the autobiography of the most lethal sniper in U.S. military history - Kyle, Chris, 1974-; McEwen, Scott; DeFelice, Jim, 1956- (New York : W. Morrow, 2012)
The astonishing autobiography of SEAL Chief Chris Kyle, whose record 150 confirmed kills make him the most deadly sniper in U.S. military history
Prologue: Evil in the crosshairs -- Bustin' broncs and other ways of having fun -- Jackhammered -- Takedowns -- Five minutes to live -- Sniper -- Dealing death -- Down in the shit -- Family conflicts -- The punishers -- The devil of Ramadi -- Man down -- Hard times -- Mortality -- Home and out
Keywords: Kyle, Chris, -- 1974-; United States. -- Navy. -- SEALs -- Biography; Iraq War, 2003-2011 -- Personal narratives, American; Snipers -- United States -- Biography